Refugee Repatriation During Conflict: A New Conventional Wisdom - Barbero, Julie C. (Refuge: Canada’s Journal on Refugees, 1993)
There are over 16.5 million refugees and people in refugee-like situations around the world, most of them in Africa. In fact, according to the World Refugee Survey, there are a total of 5,340,800 people in Africa who can be classified as refugees, asylum seekers and people in refugee-like situations who require international protection and/or assistance. Consequently, close to one in every three such persons is of African origin (Hamilton 1992, 33).